Bio-crude oil from hydrothermal liquefaction of wastewater microalgae in a pilot-scale continuous flow reactor. (December 2019) - Cheng, Feng; Jarvis, Jacqueline M.; Yu, Jiuling; Jena, Umakanta; Nirmalakhandan, Nagamany; Schaub, Tanner M.; Brewer, Catherine E.
Highlights: A continuous flow reactor was modified for producing algal bio-crude oil. Bio-crude oil (28 wt% yield, 39 MJ/kg) was obtained from wastewater algae. Bio-crude oil quality from new reactor was comparable to oils from batch reactors. Abstract: To explore the feasibility of scaling up hydrothermal liquefaction (HTL) of algal biomass, a pilot-scale continuous flow reactor (CFR) was operated to produce bio-crude oil from algal biomass cultivated in urban wastewater. The CFR system ran algal slurry (5 wt.% solids loading) at 350 °C and 17 MPa for 4 h without any clogging issues. Bio-crude oil chemistry was characterized by high-resolution Fourier transform mass spectroscopy (FT-MS), proton nuclear magnetic resonance spectroscopy ( 1 H NMR), bomb calorimetry, and elemental analysis. Bio-crude oil yield of 28.1 wt% was obtained with higher heating values of 38–39 MJ/kg. The quality of light bio-crude oil produced from the CFR system was comparable in terms of molecular structures to bio-crude oil produced in a batch reactor.